2021
DOI: 10.1101/2021.01.05.21249237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enisamium is an inhibitor of the SARS-CoV-2 RNA polymerase and shows improvement of recovery in COVID-19 patients in an interim analysis of a clinical trial

Abstract: Pandemic SARS-CoV-2 causes a mild to severe respiratory disease called Coronavirus Disease 2019 (COVID-19). Control of SARS-CoV-2 spread will depend on vaccine-induced or naturally acquired protective herd immunity. Until then, antiviral strategies are needed to manage COVID-19, but approved antiviral treatments, such as remdesivir, can only be delivered intravenously. Enisamium (laboratory code FAV00A, trade name Amizon®) is an orally active inhibitor of influenza A and B viruses in cell culture and clinicall… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…One study was originally included, but was later retracted due to concerns about data integrity, and thus was excluded [42]. Antiviral treatments compared in the included studies were umifenovir (Arbidol) [25,29,31,47], baloxavir marboxil [30], enisamium [50], SARs-CoV-2 OR SARs OR COVID-19 OR "coronavirus" OR covid AND ("antiviral drugs") AND (RCT OR "randomized controlled trial" OR "randomised controlled trial") PubMed 12-04-2021 14…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study was originally included, but was later retracted due to concerns about data integrity, and thus was excluded [42]. Antiviral treatments compared in the included studies were umifenovir (Arbidol) [25,29,31,47], baloxavir marboxil [30], enisamium [50], SARs-CoV-2 OR SARs OR COVID-19 OR "coronavirus" OR covid AND ("antiviral drugs") AND (RCT OR "randomized controlled trial" OR "randomised controlled trial") PubMed 12-04-2021 14…”
Section: Resultsmentioning
confidence: 99%
“…One study was originally included, but was later retracted due to concerns about data integrity, and thus was excluded [ 42 ]. Antiviral treatments compared in the included studies were umifenovir (Arbidol) [ 25 , 29 , 31 , 47 ], baloxavir marboxil [ 30 ], enisamium [ 50 ], favipiravir [ 25 , 30 , 35 , 40 42 , 44 , 45 , 48 , 52 ], lopinavir/ritonavir (LPV/r) [ 24 , 26 , 27 , 29 , 31 , 37 , 38 , 44 , 47 ], remdesivir [ 23 , 34 , 36 , 39 , 51 , 53 ], ribavirin [ 22 ], sofosbuvir/daclatasvir [ 22 , 32 , 33 , 46 , 49 ], sofosbuvir/ledipasvir [ 28 ], sofosbuvir/ravidasvir [ 46 ], and sofosbuvir/velpatasvir [ 43 ]. The study characteristics and baseline patient characteristics are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even those drugs with weak pharmaceutical activity toward SARS-CoV-2 work well at the early stages of infection when multiplication of viruses occurs. For example, Enisamium iodide, an isonicotinic acid derivative, which was reported as an inhibitor of RdRp of influenza A and B virus strains, recently was suggested to have the potential to prevent severe development of COVID-19 by inhibiting RNA synthesis of SARS-CoV-2 [ 148 , 149 , 150 , 151 , 152 ]. Moreover, Enisamium can directly inhibit influenza and SARS-CoV2 RNA replication, and recent clinical trials showed that COVID-19 patients recover faster and safer when prescribed with Enisamium compared to the placebo group [ 152 ].…”
Section: Beyond the Nature—antiviral Pharmaceuticalsmentioning
confidence: 99%
“…For example, Enisamium iodide, an isonicotinic acid derivative, which was reported as an inhibitor of RdRp of influenza A and B virus strains, recently was suggested to have the potential to prevent severe development of COVID-19 by inhibiting RNA synthesis of SARS-CoV-2 [ 148 , 149 , 150 , 151 , 152 ]. Moreover, Enisamium can directly inhibit influenza and SARS-CoV2 RNA replication, and recent clinical trials showed that COVID-19 patients recover faster and safer when prescribed with Enisamium compared to the placebo group [ 152 ]. Meantime, the popular antiviral composition Lopinavir/Ritonavir (HIV 3CLpro inhibitors) and other HIV protease inhibitors did not reveal any efficacy to improve the outcomes of COVID-19 patients based on multiple studies [ 153 , 154 , 155 ].…”
Section: Beyond the Nature—antiviral Pharmaceuticalsmentioning
confidence: 99%